2012
DOI: 10.1002/pa.1428
|View full text |Cite
|
Sign up to set email alerts
|

Crisis leadership styles—Bligh versus Gillard: a content analysis of Twitter posts on the Queensland floods

Abstract: This paper presents a quantitative and qualitative content analysis of Twitter posts mentioning Queensland Premier Anna Bligh and Australian Prime Minister Julia Gillard during the 2011 Queensland flood crisis. The contrast in the perceived styles of the two leaders is analysed using the theory of transformational leadership as a framework. The implications for effective leadership communication in a crisis are discussed, notably, strategies for instilling pride and gaining respect and trust. The study also hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 19 publications
0
22
0
3
Order By: Relevance
“…It suggests, at the very least, that mayors are evaluated even in situations where they have no direct political responsibility. Research on the crisis leadership styles on the Queensland floods (De Bussy et al., ) presented similar findings, where Queensland Premier Anna Bligh was perceived to be inspirational and charismatic and Australian Prime Minister Julia Gillard ‘s communication style was characterized as ‘robotic and rehearsed’. One is, therefore, not only evaluated on the basis of direct political responsibility and actions.…”
Section: Discussionmentioning
confidence: 80%
“…It suggests, at the very least, that mayors are evaluated even in situations where they have no direct political responsibility. Research on the crisis leadership styles on the Queensland floods (De Bussy et al., ) presented similar findings, where Queensland Premier Anna Bligh was perceived to be inspirational and charismatic and Australian Prime Minister Julia Gillard ‘s communication style was characterized as ‘robotic and rehearsed’. One is, therefore, not only evaluated on the basis of direct political responsibility and actions.…”
Section: Discussionmentioning
confidence: 80%
“…The ‘2011 Brisbane Floods’, however, appear to have been a turning point in changing this approach. This disaster became a major political liability, placing massive strain on the country's overall economy (Van den Honert and McAneney, ; Biggs, ; de Bussy and Paterson, ). In response, the Federal Government redrafted the NDRRA to put greater onus on State Governments to take out disaster insurance, while temporary levies were established to fund the recovery period (Biggs, ).…”
Section: The ‘Other’ Disaster Actorsmentioning
confidence: 99%
“…Compared with 14 studies based on US cases, we found six studies discussing crises outside the United States: one Australian case on the Queensland floodings (De Bussy & Paterson, ), a volcano eruption in Montserrat (Haynes, Barclay, & Pidgeon, ), a comparison of a tornado in Birmingham, UK, with a fireworks explosion in Enschede, the Netherlands (Noordegraaf & Newman, ), and riots and crowd control at a hospital in Israel (Pinkert, Bloch, Schwartz, Ashkenazi, Nakhleh, Massad, & Bar‐Dayan, ). One study discussed crisis management after an airplane crash in Amsterdam, the Netherlands (Boin & 't Hart, ).…”
Section: Resultsmentioning
confidence: 99%
“…Others studies note that mayors and governors were meant to provide hope for the future (Noordegraaf et al., ; Pennebaker & Lay, ). In like fashion, Queensland Premier Anna Bligh actively called upon Queenslanders' resilience and pride (De Bussy et al., ). This study suggested that her perceived successful leadership was largely due to charisma and inspiration.…”
Section: Resultsmentioning
confidence: 99%